Impact of local government competition and land finance on haze pollution: empirical evidence from China - Cao, Jianhong; Law, Siong Hook; Wu, Desheng; Yang, Xiaodong (Routledge, 2022)
Taking 269 prefecture-level cities in China from 2004 to 2017 as the sample dataset, this research employs spatial analysis techniques to investigate the roles of local government competition and land finance on haze pollution. The paper concludes that a significant spatial spillover and time lag are associated with haze pollution. Local government competition and land finance positively relate to haze pollution in the local area, but also produce the same effect on neighboring areas. Local government competition positively moderates the contribution of land finance to haze pollution both locally and in neighboring areas. Moreover, the role of local government competition on haze pollution is significantly negative in the east region, while significantly positive in the central-west region. The impact of land finance on haze pollution in the east region is negative but insignificant, while significantly positive in the central-west region. Local government competition positively and negatively moderates the role of land finance in the east region on haze pollution, while in the central-west region the role is significantly positive. This study provides new research ideas and empirical reference evidence for alleviating haze pollution, which is valuable for accelerating the improvement of China’s environmental quality.